Incel Epistemology: On Marginality, Experience and Legitimization of Knowledge - Johansson, Wilén Evelina (Young (Stockholm, Sweden), 2025)
This article contributes to the growing corpus of knowledge concerning the incel movement by scrutinizing how claims of marginalization are mobilized in online incel communities to present incels as privileged subjects of knowledge. The study elucidates how incel marginalization is wielded as a legitimizing experience, conferring epistemic privilege upon self-identifying incels by distinguishing between an ‘us’ of marginalized and enlightened incels, and a ‘them’ consisting of duped and privileged ‘others’. It also examines the role of partaking in incel discussions and incel ideology to achieve an incel standpoint, where lived experience is transformed into counter-hegemonic knowledge. Inspired by social movement theory, the article points to similarities between the incel movement’s political mobilization of marginalized experience and feminist standpoint theory and feminist practices in consciousness-raising groups. It argues that this affinity can be understood from the perspective of the dynamic between movements and counter-movements and their tendency to mimic and copy each other’s tactics.